Effect of Hemodialysis Adequacy on Quality of Life in Older adults with Chronic Kidney Disease - Virgianti Nur Faridah; Muhamad Syukri Ghozali; Arifal Aris; Siti Sholikhah; Masunatul Ubudiyah (Indonesian Journal of Community Health Nursing, 2021)
Introduction: Assessment of hemodialysis adequacy is an important indicator to assess the effectiveness of hemodialysis measures that can affect the patient's quality of life with chronic kidney disease. This study aims to determine the relationship between adequate hemodialysis and the quality of life of patients with chronic kidney disease undergoing hemodialysis therapy.Method: This type of research is a correlational study with a cross sectional approach. The population in this study were 86 elderly patients who underwent hemodialysis at the Muhammadiyah Lamongan Hospital. In this study, the independent variables were adequate hemodialysis and quality of life as the dependent variable. Measurement of hemodialysis adequacy was carried out using the URR formula, and the assessment of quality of life using the SF 36 questionnaire. Data analysis methods used the Spearman test using SPSS Ver. 16Result: The results of measurement of adequacy of 86 respondents, namely 13.9% achieved adequate and 86% did not achieve adequacy. The results of the quality of life assessment showed that 17.4% had a good quality of life and 82.5% had a poor quality of life. The results of statistical tests showed that there was a significant relationship between adequate hemodialysis and quality of life (p value = 0.000).Conclusion: The role of nurses is very important in improving the quality of care in achieving adequate adequacy so that it will improve the quality of life in patients with chronic kidney disease undergoing hemodialysis therapy.